Development of a New Nonbuckling Segmented Brace - Hao, Hong (World Scientific Publishing Co. Pte Ltd, 2015)
This paper introduces a new design of segmented nonbuckling brace member for use in frame structures to resist earthquake loading. The proposed segmented brace member consists of one or more segments connected by either tension-only or compressive force controlled joints. Because it cannot resist or can only resist a limited amount of compressive force, it is effective only under tension, but buckling would not be a failure mechanism of the brace. Its capability of mitigating seismic responses remains effective throughout the entire ground excitation duration. The other advantages of this new design include light weight, easy installation, easy replacement, controlled damage locations, and minimum or no residual structural deformation. The disadvantage is that full energy dissipations can be achieved only when it is in tension. Therefore they will be effective in a frame structure only when cross bracings are used. This paper presents experimental tests and numerical simulation results to examine the effectiveness of this innovative brace member in mitigating seismic responses of frame structures. Laboratory cyclic loading tests on a single brace member and on steel frames without bracing or with cross bracing by conventional brace or segmented brace are carried out. The testing results are analyzed and compared. The effectiveness of segmented brace members in mitigation of seismic loading effects on frame structures is demonstrated. Nonlinear response analyses are then carried out to investigate the performance of this new segmented brace applied to a steel frame structure subjected to ground motions of different amplitudes. The results demonstrate that this new design is effective in mitigating seismic loading effect throughout the entire ground motion duration.